Probiotic Properties of Lactic Acid Bacteria with High Conjugated Linoleic Acid Converting Activity Isolated from Jeot-Gal, High-Salt Fermented Seafood - Nho-Eul Song (MDPI AG, 2021)
Conjugated linoleic acid (CLA) isomers are potent health-promoting fatty acids. This study evaluated the probiotic properties of 10 strains of high CLA-producing lactic acid bacteria (LAB) isolated from Jeot-gal, a high-salt, fermented seafood. Two isolates, Lactiplantibacillus plantarum JBCC105683 and Lactiplantibacillus pentosus JBCC105676, produced the largest amounts of CLA (748.8 and 726.9 μg/mL, respectively). Five isolates, L. plantarum JBCC105675, L. pentosus JBCC105676, L. pentosus JBCC105674, L. plantarum JBCC105683, and Lactiplantibacillus paraplantarum JBCC105655 synthesized more cis-9, trans-11-CLA than trans-10, cis-12-CLA (approximately 80:20 ratio). All the strains survived severe artificial acidic environments and showed antimicrobial activity and strong adhesion capability to Caco-2 cells as compared to the commercial strain Lactocaseibacillus rhamnosus GG. Among them, Pediococcus acidilactici JBCC105117, L. paraplantarum JBCC105655, and L. plantarum JBCC105683 strongly stimulated the immunological regulatory gene PMK-1 and the host defense antimicrobial peptide gene clec-60 in Caenorhabditis elegans. Moreover, three strains showed a significant induction of tumor necrosis factor-α, interleukin (IL)-1β, IL-6, IL-12, and IL-10 production in RAW 264.7 macrophages, indicating that they were promising candidates for probiotics with high CLA-converting activity. Our results indicate that the newly isolated CLA-producing LAB might be useful as a functional probiotic with beneficial health effects that modulate the immune system.